2020
DOI: 10.1111/ijpo.12653
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between pancreas steatosis and the risk of metabolic syndrome and insulin resistance in Chinese adolescents with concurrent obesity and non‐alcoholic fatty liver disease

Abstract: Summary Background The incidence of childhood obesity and associated comorbidities are on an increasing trend worldwide. More than 340 million children and adolescents aged between 5 and 19 years old were overweight or had obesity in 2016, from which over 124 million children and adolescents (6% of girls and 8% of boys) had obesity. Objective To describe the relationship between pancreas steatosis, body fat and the risk of metabolic syndrome, insulin resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 51 publications
1
12
0
3
Order By: Relevance
“…There are conflicting studies in the literature about the association between abdominal fat and hepatic fat content [22,[25][26][27]. Sharma et al observed statistically significant correlations among liver fat fraction, BMI and SAT [22].…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting studies in the literature about the association between abdominal fat and hepatic fat content [22,[25][26][27]. Sharma et al observed statistically significant correlations among liver fat fraction, BMI and SAT [22].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the fatty liver, in which lipid droplets accumulate in the cytoplasm in the hepatocytes, pancreatic fatty infiltration involves the fat cells (adipocytes) ectopically developing and accumulating in and around the pancreatic lobules alongside the exocrine and endocrine tissues. The fat content in the pancreas increases with age ( 90 ) and is detectable as early as in adolescence ( 91 ), and the degree is linked with obesity ( 92 94 ). In the progression from obesity to type 2 diabetes, the state of hyperinsulinemia is likely to accelerate the pancreatic fat accumulation due to the organ’s high insulin concentration.…”
Section: Sample Processingmentioning
confidence: 99%
“…Тесную взаимосвязь между НАЖБП, НАЖБПЖ, МС и ИР подчеркивают китайские ученые [14]. Обследовав 52 подростка с ожирением и НАЖБП в возрасте 14-18 лет, исследователи распределили детей на две в группы в зависимости от наличия/ отсутствия МРТ-признаков НАЖБПЖ (протонная плотность жировой фракции ≥5%).…”
Section: нажбпж и ссз сдunclassified
“…Развитие стеатоза ПЖ на фоне ожирения ассоциировано с ИР (OШ 1,58; 95% ДИ 0,39-6,4) и МС (OШ 1,70; 95% ДИ 0, 5). Авторы этой работы предлагают рассматривать стеатоз ПЖ не как доброкачественную находку, обнаруженную в ходе визуализирующего исследования, а считать его биомаркером прогрессирующей метаболической и эндокринной дисфункции ПЖ [14].…”
Section: нажбпж и ссз сдunclassified